Rare Virulences and Great Pathotype Diversity of a Central European Blumeria hordei Population - Dreiseitl, Antonín (Journal of fungi (Basel, Switzerland), 2023)
Barley is an important crop grown on almost 49 Mha worldwide in 2021 and is particularly significant in Europe where powdery mildew is the most frequent disease on susceptible varieties. The most suitable way to protect crops is by exploiting genetic resistance. However, the causal agent Blumeria hordei is an extremely adaptable pathogen. The aims of this research were to increase our knowledge of the rapidly changing pathogen population and detect rare virulences. Random samples of the pathogen were obtained from the air by means of a mobile spore sampler. Spores were collected by driving across the Czech Republic in 2019, 2021 and 2023, and 299 isolates were analyzed on 121 host varieties. No infection occurred on 35 differentials, rare virulence was recorded on 31 varieties and a higher virulence frequency was found on 55 differentials. A core set of differentials along with four additional varieties distinguishes 295 pathotypes (Simple Index = 0.987) and the virulence complexity of isolates varied from 4 to 19 with an average of 10.39. The detection of new virulences, the increasing frequency of previously rare virulences and high pathotype diversity as well as high virulence complexity confirm that using nonspecific durable resistance is crucial for successfully breeding commercial varieties.
Keywords: reverse octal notation; barley; Blumeria graminis f. sp. hordei; virulence frequency; powdery mildew; resistance genes; Hordeum vulgare; virulence complexity